National security, leaks, and freedom of the press : the Pentagon papers fifty years on - Bollinger, Lee C., 1946-; Stone, Geoffrey R. (New York, NY : Oxford University Press, 2021)
This publication draws on the expertise of an extraordinary group of national security officials, journalists and academics to explore the issue first posed half-a-century ago in the Pentagon Papers decision: To what extent does the First Amendment give government employees, journalists and other entities a First Amendment right to disclose, to obtain or to publish classified information relating to the national security of the United States? The authors offer deeply informed, thoughtful, and often surprising proposals for how to cope with these challenges in a twenty-first century democracy.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 9, 2021).
Keywords: Government information -- Law and legislation -- United States; Public records -- Access control -- United States; National security -- Law and legislation -- United States; Security classification (Government documents) -- United States; Leaks (Disclosure of information) -- United States -- History; Freedom of the press -- United States; Government and the press -- United States; Pentagon Papers; Snowden, Edward J., -- 1983-